AKTIVITAS ANTIHIPERGLIKEMI DAN REGENERASI SEL Î² PANKREAS DARI FRAKSI ETIL ASETAT DAUN KERSEN (Muntingia calabura) PADA TIKUS YANG DIINDUKSI STREPTOZOTOSIN - PRATAMA, KHARISMA; Wicahyo , Septian Maulid; Hidayat, Rahmad (Universitas Duta Bangsa Surakarta, 2024)
Normal blood glucose levels and antioxidant activity are the keys to preventing Diabetes Mellitus and its complications. Some herbal plants have this activity. Cherry leaves (Muntingia calabura) are plants around us that have empirical uses, one of which is lowering blood glucose. The aim of the research was to determine the activity of the ethyl acetate fraction of cherry leaves in reducing blood glucose and improving pancreatic beta cells. Forty-two 8-week-old male Wistar rats weighing 180-200 g were induced with diabetes using streptozotocin and divided randomly. Group I was normal control, group II was negative control, control III was positive control using glibenclamide, groups IV and V tested ethyl acetate fractions 250 and 350 mg/kg BW. Treatment is carried out orally once a day for 18 days. Glucose levels were measured on days 1, 4, 11 and 18. The results showed that the extract and fractions could reduce blood glucose levels with the 350 mg/kg BW ethyl acetate fraction reducing the highest (not significantly different from the positive control) and both could increase the activity of the SOD, GPx enzymes and reduce MDA levels and improve pancreatic Langerhans islets. In conclusion, cherry leaf extract and fractions have antihyperglycemic activity and pancreatic islet regeneration.